A Racemic and Enantiopure Unsymmetric Diiron(III) Complex with a Chiral o‐Carborane‐Based Pyridylalcohol Ligand: Combined Chiroptical, Magnetic, and Nonlinear Optical Properties. Issue 4 (12th December 2013) - Di Salvo, Florencia; Tsang, Min Ying; Teixidor, Francesc; Viñas, Clara; Planas, José Giner; Crassous, Jeanne; Vanthuyne, Nicolas; Aliaga‐Alcalde, Núria; Ruiz, Eliseo; Coquerel, Gerard; Clevers, Simon; Dupray, Valerie; et al.
Abstract The design of molecule‐based systems combining magnetic, chiroptical and second‐order optical nonlinear properties is still very rare. We report an unusually unsymmetric diiron(III) complex 1, in which three bulky chiral carboranylpyridinealkoxide ligands (oCBhmp−) bridge both metal ions and the complex shows the above‐mentioned properties. The introduction of o‐carborane into the 2‐(hydroxymethyl)pyridine (hmpH) architecture significantly alters the coordination of the simple or aryl‐substituted 2‐hmpH. The unusual architecture observed in 1 seems to be triggered by the poor nucleophilicity of our alkoxide ligand (oCBhmp−). A very rare case of spontaneous resolution takes place on precipitation or exposure to solvent vapor for the bulk compound, as confirmed by a combination of single‐crystal and powder X‐ray diffraction, second‐harmonic generation, and circular dichroism. The corresponding enantiopure complexes (+)1 and (−)1 have also been synthesized and fully characterized. This research provides a new building block with unique geometry and electronics to construct coordination complexes with multifunctional properties.